1983
DOI: 10.1007/bf02480982
|View full text |Cite
|
Sign up to set email alerts
|

The future occurrence of records

Abstract: SummaryThe occurrence of future record values based on data from a sequence of independent, identically distributed random variables is considered. Two situations are analysed, namely (i) where only the first m record observations have been noted, and (ii) where all the observations have been noted up to the ruth record. Tolerance regions and Bayesian predictive distributions are derived for the increase in size of the (m-}-r)th record value over the observed ruth record value for two exponential models. Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Consider a data set discussed by Dunsmore (1983). A rock crushing machine is kept working as long as the size of the crushed rock is larger than the rocks crushed before.…”
Section: A Real Examplementioning
confidence: 99%
“…Consider a data set discussed by Dunsmore (1983). A rock crushing machine is kept working as long as the size of the crushed rock is larger than the rocks crushed before.…”
Section: A Real Examplementioning
confidence: 99%
“…Consider a data set concerning the rock crushing machine which was reported by Dunsmore (1983) as a real data set where comes from the exponential distribution. A rock crushing machine has to be reset if at any operation the size of the rock being crushed is larger than the rock that has been crushed before.…”
Section: Real Examplementioning
confidence: 99%
“…Several authors have studied the subject of predicting future records on the basis of observed records from the same distribution. See for example, Ahsanullah (1980), Dunsmore (1983), Awad and Raqab, Mohammad (2000), Ali Mousa et al (2002), Ahmadi et al (2005), Ahmadi and Doostparast (2006), Raqab (in press), Raqab and Balakrishnan (2008), Ahmadi et al (in press) and the references therein. Thus, so far, researchers have considered prediction of records based on records and prediction of order statistics based on order statistics.…”
Section: Introductionmentioning
confidence: 96%